Awareness of dental health among children with different socioeconomic status - A Questionnaire - CHANCHAL KATARIYA,; Dr.GANESH JEEVANANDAN, (International Journal of Pharma and Bio Sciences, 2018)
The aim of the study is to assess the dental knowledge among children with different socioeconomic status. The objective of the study is to determine the prevalence of dental knowledge among children between age of 10-15years with different socioeconomic status. Many reviews and research documents the relationship between socioeconomic status and the health eduction of an individual and consistently finds an inverse relationship between socioeconomic status and the incidence and prevalence of disease: that is, as socioeconomic status increases, disease, illness, and their impacts decrease. The purpose of the study is to determine the level of dental knowledge in a given indian population with difference in socioeconomic status.